Patrilineal populations show more male transmission of reproductive success than cognatic populations in Central Asia, which reduces their genetic diversity. Issue 4 (27th March 2015) - Heyer, Evelyne; Brandenburg, Jean‐Tristan; Leonardi, Michela; Toupance, Bruno; Balaresque, Patricia; Hegay, Tanya; Aldashev, Almaz; Austerlitz, Frederic
ABSTRACT Objective: The extent to which social organization of human societies impacts the patterns of genetic diversity remains an open question. Here, we investigate the transmission of reproductive success in patrilineal and cognatic populations from Central Asia using a coalescent approach. Methods: We performed a study on the mitochondrial DNA (mtDNA) and Y chromosome polymorphism of patrilineal and cognatic populations from Central Asia. We reconstructed the gene genealogies in each population for both kind of markers and inferred the imbalance level of these genealogies, a parameter directly related to the level of transmission of reproductive success. Results: This imbalance level appeared much stronger for the Y chromosome in patrilineal populations than in cognatic populations, while no difference was found for mtDNA. Furthermore, we showed that this imbalance level correlates negatively with Y‐chromosomal, mtDNA, and autosomal genetic diversity. Conclusions: This shows that patrilineality might be one of the factors explaining the male transmission of reproductive success, which, in turn, lead to a reduction of genetic diversity. Thus, notwithstanding the fact that our population genetic approach clearly shows that there is a strong male‐biased transmission of reproductive success in patrilineal societies, it also highlights the fact that a social process such as cultural transmission of reproductive success could play an important role in shaping human genetic diversity, although we cannot formally exclude that this transmission has also a genetic component. Am J Phys Anthropol 157:537–543, 2015. © 2015 Wiley Periodicals, Inc.